2021
DOI: 10.3390/ijms22179395
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Network of Sturgeon Chondroitin Sulfate on Colorectal Cancer Inhibition by Transcriptomic and Proteomic Analysis

Abstract: Chondroitin sulfate (CS) is a food-derived bioactive substance with multiple biological functions, which exists in animal cartilage and/or bone. Sturgeon, a type of cartilaginous fish, is rich in CS. Our recent study demonstrated the effect of sturgeon chondroitin sulfate (SCS) on reducing colorectal cancer cell proliferation and tumor formation. However, the molecular mechanisms of its anticancer activity remain unknown. In this study, the cell proliferation assay and flow cytometric analysis were used to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Oral supplementation of CS is well-tolerated by humans with favorable pharmacokinetics. Although CS has shown some beneficial effects to suppress colon cancer cell growth in vitro 48 , 49 , 50 , the molecular mechanism was not defined. Here, we found CS treatment in vitro or in vivo attenuated Papss2 deficiency-induced and APC deficiency-responsive gut tumorigenesis through the inhibition of Wnt/ β -catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Oral supplementation of CS is well-tolerated by humans with favorable pharmacokinetics. Although CS has shown some beneficial effects to suppress colon cancer cell growth in vitro 48 , 49 , 50 , the molecular mechanism was not defined. Here, we found CS treatment in vitro or in vivo attenuated Papss2 deficiency-induced and APC deficiency-responsive gut tumorigenesis through the inhibition of Wnt/ β -catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of gene functions and pathways involved in necroptosis-related lncRNAs, previous studies have found that genetic variation in the citric acid cycle and fatty acid metabolism are associated with the onset and progression of CC ( Choi et al, 2019 ; Cho et al, 2020 ). Chondroitin sulfate has certain effects on the proliferation and apoptosis of CC ( Wu et al, 2021 ). The GSEA of this study found that the differentially expressed necroptosis-related lncRNAs in the high-risk group and the low-risk group were involved in the process of gene recombination, tumor cell proliferation, antigen processing and presentation, and nutrient metabolism in CC, thereby affecting the occurrence and progression of CC.…”
Section: Discussionmentioning
confidence: 99%